Pengembangan media pembelajaran literasi digital interaktif pada materi persebaran flora dan fauna - Titip Prayoga; Yusuf Suharto; Didik Taryana (Universitas Negeri Malang, 2022)
The lack of interactive learning media in learning Geography builds researchers’ intention to create effective learning media used in the learning process. One of the appropriate learning media with current technological advances is interactive digital literacy learning media. The development of this digital literacy learning media has the aim of improving the quality of Geography learning. At this media development stage includes eight development sequences including: (1) needs analysis, (2) preparation of learning media objectives, (3) collection of material items, (4) formulation of product assessment instruments, (5) making media, (6) implementation of the test, (7) revision, and (8) the final product. The product validity test was carried out by three experts, the first being a media expert who scored 100 percent with the validity criteria